Above Room-Temperature Ferromagnetism in Wafer-Scale Two-Dimensional van der Waals Fe3GeTe2 Tailored by a Topological Insulator - Wang, Haiyu; Liu, Yingjie; Wu, Peichen; Hou, Wenjie; Jiang, Yuhao; Li, Xiaohui; Pandey, Chandan; Chen, Dongdong; Yang, Qing; Wang, Hangtian; Wei, Dahai; Lei, Na; et al. (ACS nano, 2020)
The emerging two-dimensional ferromagnetic materials present atomic layer thickness and a perfect interface feature, which have become an attractive research direction in the field of spintronics for low power and deep nanoscale integration. However, it has been proven to be extremely challenging to achieve a room-temperature ferromagnetic candidate with well controlled dimensionality, large-scale production, and convenient heterogeneous integration. Here, we report the growth of wafer-scale two-dimensional Fe3GeTe2 integrated with a topological insulator of Bi2Te3 by molecular beam epitaxy, which shows a Curie temperature (T c ) up to 400 K with perpendicular magnetic anisotropy. Dimensionality-dependent magnetic and magnetotransport measurements find that T c increases with decreasing Fe3GeTe2 thickness in the heterostructures, indicating an interfacial engineering effect from Bi2Te3. The theoretical calculation further proves that the interfacial exchange coupling could significantly enhance the intralayer spin interaction in Fe3GeTe2, hence giving rise to a higher T c . Our results provide great potential for the implementation of high-performance spintronic devices based on two-dimensional ferromagnetic materials.